An Indian Past of the Great War: Subaltern History in Across the Black Waters. (July 2015) - Bijral, Quleen Kaur
The Indian past of the Great War is a subaltern record that either has not been investigated or left forgotten and unacknowledged in the annals of Indian history. In order to deconstruct the polemics of this intentional or inadvertent loophole of history, the objective of the paper is to invest the Indian history of the Great War in the historiography of India's independence struggle. Gayatri Spivak, in her essay Can the Subaltern Speak attempted to invest the subaltern with a historical agency. It is an indispensable notion that intends to resolve the discrepancies, the invalidity and glaring lacunae in the Indian history.